The Effect of Health Webinars to Increase Parents' Knowledge about Fulfilling Children's Nutrition - Ferdian, Dani; Hikmat, Rohman; Noviana, Mikha; Ma’ruf, Tisa Layalia Hanifah; Sadjugo, Ito Purwanto (Journal of Language and Health, 2024)
The fulfillment of children's nutrition is an important aspect in supporting children's optimal growth and development. Parents play a crucial role in providing healthy and nutritious food for their children. However, parents' knowledge about child nutrition may not always be adequate, which can impact children's health and well-being. Objective: This study aims to determine the effect of webinars as a health education method on parents' knowledge about fulfilling children's nutrition at TK Hati Nurani. Methods: This study used a quantitative design with a quasi-experimental approach. The sampling technique uses total sampling. The study sample consisted of 15 parents at TK Hati Nurani. Data were collected through organizing webinars and distributing online questionnaires. Data were analyzed using descriptive statistics and t-test. Results: the results showed that although webinars as a health education method were conducted, there was no significant change in parents' knowledge about child nutrition. The results highlight the possibility of factors such as unfamiliarity with technology and limited access to or understanding of technology affecting the effectiveness of webinars in improving parental knowledge. Conclusion: There is a need for in-depth evaluation of the design and implementation of webinars as a health education method. Nonetheless, the importance of health education as an effort to increase parents' knowledge and awareness about fulfilling children's nutrition is still emphasized.